Analisis dan Peran Pendidikan Kewarganegaraan Dalam Menangani Persoalan Bullying - Randi, Muhammad Sinar; Wulandari, Astri; Lubis, Ocha Shafiqah Putri; Husnida, Windy Annisa; Barus, Nabila Qhassy Br (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Citizenship Education (PKn) in schools is very important for forming the character of students and plays a strategic role in increasing the potential of the young generation to become good and democratic citizens based on Pancasila and the 1945 Constitution. This research will discuss the role of Civics in overcoming bullying at school and on social media. , with special emphasis on how best to implement Civics to prevent bullying behavior. This research uses library research as its method. The research results show that, both directly and indirectly, citizenship education plays an important role in overcoming bullying. Citizenship education can help students become more aware of themselves as citizens, understand their rights and obligations as citizens, and learn to handle different situations, including harassment.